Feasibility Study on Re-Using Tennis Balls as Seismic Isolation Bearings - Katsamakas, Antonios A.; Chollet, Miro; Eyyi, Stefan; Vassiliou, Michalis F. (Frontiers in Built Environment, 2021)
This paper presents an experimental study of a low-cost seismic isolator that can be used for the protection of residential structures in low-income countries. The isolator is based on mortar-filled, used tennis spheres, rolling on flat or spherical concrete surfaces. The tennis spheres serve as a permanent, spherical mold to cast mortar, and they are not removed after casting. The thin rubber shell of the tennis sphere offers increased damping and reduces stress concentrations at the contact areas. At the same time, this procedure creates a promising solution for the re-use of tennis spheres. Using a closely spaced grid of such spheres may allow for avoiding the diaphragm slab at the isolation level, or reducing its thickness. Avoiding the cost of this additional, heavily reinforced isolation slab is crucial for making seismically isolated low-rise dwellings economically feasible in low-income regions of the globe. Initially, the tennis isolators were subjected to monotonic uniaxial compression to examine their behavior under vertical loading. Different mixes and low-cost reinforcement approaches to increase their strength were tested. Subsequently, cyclic tests were performed to obtain the lateral force-displacement diagram of the isolation system. The effects of the geometry of the rolling surface (i.e., flat or concave) and of the applied compressive load (i.e., 2.08, 3.23, 4.74, or 8 kN/sphere) on the cyclic behavior were investigated. It was found that the restoring force of such systems mainly originates from the curvature of the concrete surface. However, the vertical motion induced by the compressed sphere and its local casting imperfections is not negligible. When surface imperfections become significant, the force-displacement loops deviate from the bilinear curves that a rigid-body model suggests. When the spheres are properly cast, they experience zero damage even under 8 kN of compressive force, and their loops have a bilinear form. For the tested configurations, the rolling friction (defined as the ratio of lateral to vertical force at zero displacement) was in the range of 5.5 % to 7.2 %, thus suitable for seismic isolation applications. The cost of the tested tennis ball isolators was 0.05 $ per sphere.